The Student’s Motivation and Outcome by ARCS (Attention, Relevance, Confidence, Satisfaction) Learning on Ecosystem Concept - Widowati, Sri; Ngabekti, Sri; Kartijono, Nugroho Edi (Journal of Biology Education, 2018)
This study aims to determine the learning of class X MA Al Asror students in biology teaching and learning activities with ARCS learning. The sample which is used is class X MIA 1 and it is determined by simple random sampling. The results of the t-test on the scores of students' learning motivation obtained sig. value of 0,000 < 0,05, r value is 0,774, and calculated t value is -16,658 which shows that there is a difference between students’ learning motivation in non-ARCS learning and students’ learning motivation in ARCS learning and there is a relationship between ARCS learning and students' learning motivation with the contribution of 60%. The increase in students’ learning motivation is analyzed by N-gain test with the average N-gain score of 0.39. The classical completeness in non-ARCS learning is 0% while in ARCS learning is 66.67%. The result of multiple correlation of learning motivation and student performance on learning outcomes show r2 of 0.241.